TRI DHARMA PERGURUAN TINGGI MENJAWAB TANTANGAN GLOBALISASI - Intan Purnamasari; Rusni Rusni (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The problem formulation of this paper is the Tri Dharma College that is and how the Tri Dharma Colleges are answering the challenges of globalization today. The purpose of this paper writing is to find out the definition of Tri Dharma College and to know how Tri Dharma colleges are addressing the challenges of today's globalization era. Entering the 21st century there are four trends of change that will affect the patterns of life. Globalization era will continue and we are therein. No rules whatsoever of any country can prevent globalization. Therefore, the state-of-the-being intellectuals in the country must prepare to confront them. One is know and understand about the three pillars of the basic mindset and the obligation for students that is Tri Dharma College. Tri Dharma Colleges is the basis of mindset and which becomes a duty for students. The responsibility given to the student is in Tri Dharma, because students have an important position for this country in the face of this globalization era. Through education and teaching become a qualified graduates who are able to deal with the excitement of the dynamics of globalization, do research and development, and the latter understand what needs community through devotion to society.